Pembinaan Program Panduan Keselamatan Berkendara pada Siswa Yayasan Sahabat Cendikia - Nofriani Fajrah; Yera Wahda Wahdi (Prosiding, 2022)
drivers today vary from men to women and from children to adults. Problems that are often found in driving and traffic such as traffic accidents, congestion, and violations of traffic signs. This condition is triggered by the lack of awareness of traffic safety driving among the public, especially for underage drivers. Sahabat Cendikia Foundation is one of the non-formal educational institutions that helps the community to obtain formal education certificates. Therefore, the Sahabat Cendikia Foundation requires the active participation of institutions that care about non-formal education as a transfer knowledge agent to enrich the knowledge and insights of students so that they are equivalent to formal education. Students at the Sahabat Cendikia Foundation are part of motorized vehicle drivers, both underage and adults. Therefore, this activity will be right on target for service participants who really need external knowledge such as this traffic safety coaching program. It is hoped that this service activity can increase the understanding of students at the Sahabat Cendikia Foundation in the traffic safety program. This service activity is carried out by providing an explanation of traffic safety guidelines such as traffic regulations and completeness in driving in traffic in order to avoid the risk of traffic accidents